电视剧《甄嬛传》台词与歌词中的诗词曲赋研究 = Research on classical poetry in script lines and Song lyrics of Chinese drama Legend of Zhenhuan - 孙宇慧 Sun, Nicole Yu Hui (2016)
中国文学中的古典元素向来以高雅著称，但在当代的影视剧和流行歌曲中却甚少被运用。然而，自 2011 年末全面爆红的古装历史剧《甄嬛传》开始，传统的古典元素受到了一定程度的追捧。可以说，《甄嬛传》的成功，除了归功于精彩的影视情节、精致的场景铺排和精湛的演员技艺，剧中严肃严谨和无处不在的古典元素也是此剧成功的关键性因素之一。本文以《甄嬛传》中经典台词和主题音乐的古典元素为研究对象，探讨这类古典诗词曲赋与中国风音乐对这部剧的影响及对当代流行文化的作用和意义。论文共分五个部分。绪论在综述近年相关文献研究的基础上，对选题意义及本文创新点作简要的阐述。第一章归纳《甄嬛传》中经典台词与古典诗词曲赋之间的关系，以此说明古典元素的使用对ᨀ升影视剧文学性的作用。第二章研究《甄嬛传》的六首大陆版主题音乐中的古典元素，以此论述其中的延异效应与陌生化效果及其与现代流行文化相结合的优劣。第三章探讨《甄嬛传》在美港台三地的不同传播现象；并对比其他几部热播的古装历史剧，剖析古典元素的多寡对这类剧的影响，从而探析古装历史剧未来的发展方向。结语总结本文所讨论的重点，从而说明台词与主题音乐中的古典元素对这部古装历史剧得以成功所起到的重要作用。Chinese literature has always been known for its elegant classical elements, yet these elements are rarely used in contemporary songs and TV dramas. However, these classical elements became highly sought-after ever since the historical costume TV drama Legend of Zhenhuan burst into popularity in 2011. Apart from the exciting plot, exquisite setting and consummate acting, the ubiquitous presence of classical elements have also contributed to the success of the drama. This thesis focuses on traditional Chinese-style music, more amicably known as ZhongGuoFeng, and the classical elements in the script and lyrics of Legend of Zhenhuan, and discusses their significance and impact on the drama and on contemporary pop culture. This thesis consists of five parts. Firstly, the introduction will explain the significance of the chosen topic based on recent research and literature reviews. Secondly, this paper attempts to draw out the connection between famous script lines and classical Chinese poetry used in the drama to explain how the use of classical elements would enhance the literary aspects of films and television drama. Thirdly, this paper studies the Différance and Defamiliarization effects of classical elements in six of China mainland’s version of the drama’s theme music and analyses the problems it poses when it meets contemporary pop culture. Fourthly, this paper discusses the propagation phenomena of Legend of Zhenhuan in United States, Hong Kong and Taiwan and compares them to other popular historical costume dramas to examine how the extent of use of classical elements can impact historical costume dramas and offers some insights on the development of such dramas in the future. The conclusion summarizes key points discussed in this paper, and attempts to explain how the use of classical elements in script lines and lyrics in Legend of Zhenhuan is an important factor, contributing to the success of this TV drama.